Therapeutic induction of antigen-specific immune tolerance - Kenison, Jessica E; Stevens, Nikolas A; Quintana, Francisco J (Nature reviews. Immunology, 2024)
The development of therapeutic approaches for the induction of robust, long-lasting and antigen-specific immune tolerance remains an important unmet clinical need for the management of autoimmunity, allergy, organ transplantation and gene therapy. Recent breakthroughs in our understanding of immune tolerance mechanisms have opened new research avenues and therapeutic opportunities in this area. Here, we review mechanisms of immune tolerance and novel methods for its therapeutic induction.